PENGARUH KOMPENSASI TERHADAP DISIPLIN KERJA KARYAWAN DI NANTONGGA BEACH HOTEL - busra, Medy eldia (journal of residu, 2019)
The study aims to determine the discipline of employees at Nantongga beach hotels which tend to fall in the last 5 months. This type of research is associative quantitative research with a simple linear regression test. The population in this study were all employees of Nantongga Beach Hotel. The research sample amounted to 30 employees during the study period with sampling techniques as quota sampling. Data collection techniques are carried out by using a questionnaire (questionnaire) with a Likert scale that has been tested for validity and reliability. Furthermore, the data were analyzed through description analysis and simple linear regression test with the help of the SPSS Computer Program version 16.00. The results of the study were: 1) Compensation of Nantongga Beach Hotel Pariaman employees showed a very dissatisfied category which was 36.67%, 2) Work discipline was in the satisfied category (56.67%), 3) Simple linear regression test results with a significance level of 0.037, there was influence positive and significant between compensation and employee work discipline with a r value of 0.519 (sig 0,000) with a significant interpretation of influence.